2018
DOI: 10.3390/jmse6020053
|View full text |Cite
|
Sign up to set email alerts
|

Marine Turbine Hydrodynamics by a Boundary Element Method with Viscous Flow Correction

Abstract: A computational methodology for the hydrodynamic analysis of horizontal axis marine current turbines is presented. The approach is based on a boundary integral equation method for inviscid flows originally developed for marine propellers and adapted here to describe the flow features that characterize hydrokinetic turbines. For this purpose, semi-analytical trailing wake and viscous flow correction models are introduced. A validation study is performed by comparing hydrodynamic performance predictions with two… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…An extension in 3D is envisioned in the near future. Another very interesting work of Salvatore et al [67], which is very close to our formulation, is also considered. However, their approach with Lagrangian vortex sheets prevents the use of the PSE-LES diffusion model as well as the presented ambient turbulence model, both of these aspects being of major importance in the present study.…”
Section: Discussionmentioning
confidence: 91%
“…An extension in 3D is envisioned in the near future. Another very interesting work of Salvatore et al [67], which is very close to our formulation, is also considered. However, their approach with Lagrangian vortex sheets prevents the use of the PSE-LES diffusion model as well as the presented ambient turbulence model, both of these aspects being of major importance in the present study.…”
Section: Discussionmentioning
confidence: 91%
“…The present results show a similar range. On the other hand, a recent study using the boundary element method by Salvatore et al [49] reported that viscous forces significantly affect TST performance characteristics for λ < 3, i.e., when the flow encounters massive flow separation and stall, but does not show significant effects for λ ≥ 5. Mason-Jones et al [8] analyzed the experimentally measured performance characteristics of model (D = 0.5 m) and full-scale (D = 10 m and 30 m) TSTs for which the Re D varied from 3 × 10 4 to 10 7 .…”
Section: Thrust and Power Predictionsmentioning
confidence: 98%
“…the resolution of which gives access to a value of the velocity potential on each face j of the mesh. We can then use Bernoulli's relation, a practice widely used in potential codes for good quality performance results outside of the regions of stall (Salvatore et al 2015, Salvatore et al 2018:…”
Section: Towards a Simulation Of The Turbine By Anmentioning
confidence: 99%